Occurrence and Distribution of Viruses Associated with Okra and Their Alternative Hosts in Kaduna and Zamfara States, Nigeria. - ZaharaddeenSamaila, Gilima; Boniface, David Kashina; Oyeleke Banwo, Olalekan; Dada, Alegbejo Mathew; Agart, Charles Chindo; Tijjani, Ibrahim (Journal of Tropical Crop Science, 2021)
One of the major constraints to production of okra (Abelmoschus esculentus L.) in Nigeria and in particular in Kaduna and Zamfara States, is the problem of okra mosaic virus and okra leaf curl virus. This study was carried out to provide information on the occurrence and distribution of okra mosaic and okra leaf curl viruses on okra, in Kaduna and Zamfara states, Nigeria. A survey of okra-producing farms was carried out during dry and wet seasons of 2017 cropping season in Kaduna (Zaria, Lere, and Igabi Local Government Areas) and Zamfara (Gusau, Bungudu, and Zurmi LGAs) states. Leaf samples (15) of symptomatic okra plants were collected from each farm in the study area. The total number of plants and the number of symptomatic plants within each subplot were recorded, and the disease incidence was determined. Double Antibody Sandwich Enzyme-Linked Immunosorbent Assay (DAS- ELISA) kit was used in the detection of Okra Mosaic Virus while Polymerase Chain Reaction (PCR) was employed for the detection Okra Leaf Curl Virus. The results showed that all the okra leaf samples tested for OLCV were negative in this study while OkMV was tested positve in all the samples with a recorded incidence of 20 % and 14 % in Kaduna and Zamfara states respectively, however, only 8 out of total weed samples were also tested positive for OKV, but all were tested negative to OLCV.